Circumpolar phylogeography and demographic history of beluga whales reflect past climatic fluctuations. Issue 11 (14th May 2021) - Skovrind, Mikkel; Louis, Marie; Westbury, Michael V.; Garilao, Cristina; Kaschner, Kristin; Castruita, José Alfredo Samaniego; Gopalakrishnan, Shyam; Knudsen, Steen Wilhelm; Haile, James S.; Dalén, Love; Meshchersky, Ilya G.; Shpak, Olga V.; et al.
Abstract: Several Arctic marine mammal species are predicted to be negatively impacted by rapid sea ice loss associated with ongoing ocean warming. However, consequences for Arctic whales remain uncertain. To investigate how Arctic whales responded to past climatic fluctuations, we analysed 206 mitochondrial genomes from beluga whales ( Delphinapterus leucas ) sampled across their circumpolar range, and four nuclear genomes, covering both the Atlantic and the Pacific Arctic region. We found four well‐differentiated mitochondrial lineages, which were established before the onset of the last glacial expansion 110 thousand years ago. Our findings suggested these lineages diverged in allopatry, reflecting isolation of populations during glacial periods when the Arctic sea‐shelf was covered by multiyear sea ice. Subsequent population expansion and secondary contact between the Atlantic and Pacific Oceans shaped the current geographic distribution of lineages, and may have facilitated mitochondrial introgression. Our demographic reconstructions based on both mitochondrial and nuclear genomes showed markedly lower population sizes during the Last Glacial Maximum (LGM) compared to the preceding Eemian and current Holocene interglacial periods. Habitat modelling similarly revealed less suitable habitat during the LGM (glacial) than at present (interglacial). Together, our findings suggested the association between climate, population size, and available habitat in belugas. Forecasts for year 2100 showed that beluga habitat will decrease and shift northwards as oceans continue to warm, putatively leading to population declines in some beluga populations. Finally, we identified vulnerable populations which, if extirpated as a consequence of ocean warming, will lead to a substantial decline of species‐wide haplotype diversity.